Cone-Beam Computed Tomography in Periodontal Diagnosis and Treatment Planning - Murali, Aparna C.; Bhandary, Rahul (Journal of Health and Allied Sciences NU, 2022)
Diagnosis of periodontal disease depends on conventional clinical parameters. In periodontitis with extensive bone defects, radiographs play a crucial role in arriving at a proper diagnosis. The emergence of cone-beam computed tomography (CBCT) became a boon in oral radiology. Limitations of conventional two-dimensional (2D) radiographs include inadequate visualization of bone defects, lamina dura, and furcation involvement. CBCT generates 3D images of anatomical structures necessary for the periodontal diagnosis of furcation involvement, intrabony defects, and implant placement. CBCT, thus, imparts various potential applications in the field of periodontics which serves to arrive at better diagnostic conclusions.
Keywords: CBCT; periodontics; implant planning; radiography